الشرط الجزائي وأثره في المعاملات المالية المعاصرة : المضاربة المشتركة أنموذجا - علي، عبد الرحمن
Among the remarkable developments of financial activities is the subject matter known as the 'penalty condition'. Contemporary jurists have intensively studied the one of which penalty condition and held three distinct opinions about it; as permissible, impermissible and subject to elaboration. The area is still open for research and analysis. This suggests that more research needs to be carried out in the area. As such, this study aims to collect and analyse as much as possible jurists' opinions on the matter. Furthermore, the study investigates penalty condition and examines its legality from the Islamic jurisprudence perspective. Moreover, the study also identifies the implementation of penalty condition in collective partnership contracts. Methodologically, both inductive and analytical approaches were employed to analyse, compare and contrast jurists' opinions and project opinions believed to be the best to the best of the researcher's knowledge according to the evidence given. Findings of the study reveal that penalty condition is permissible in all contracts except contracts in which the initial commitment resulted from debt. It is impermissible for the collective partner to guarantee any loss on it, unless it arises as a result of negligence or violation of conditions initially agreed upon. Furthermore, the findings conclude that penalty condition falls under the principle of gain accompanies liability, which is difficult to be implemented on the collective partner (Islamic bank) owing to the fact that the bank often stipulates conditions on general and in penalty conditions in particular, which suit the investment project and assist in generating more profit, which has nothing to do with clients in stipulating those conditions.